Review of testicular cancer from 2000 until 2015 in HUSM - Harun, Ahmad Khairul Irham (2018)
Background Testicular cancer is a rare malignancy worldwide, especially among Asians. Even though it is associated with 98% survival, it is mainly a disease of young adults and the incidence is increasing worldwide. There is no reported survival outcome among testicular cancer patients who are treated in Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian. This study aims to analyze the 5-years OS and PFS and associated predictive factor for survival among testicular cancer patients treated in HUSM. Methodology This is a retrospective cohort study performed in HUSM. All histopathology confirmed cases of testicular cancer are included. Patient demographics, histopathological findings of the surgical specimen, serum tumor markers, relevant radiological findings, treatment modalities received and patient survival status until 31st July 2017 were reviewed. Kaplan-Meier plot was used to calculate 5-years OS and PFS. Log-rank test and Pairwise comparison were used to calculate the survival difference between two or more groups. Univariate Cox regression analysis was used to analyze the association between predictive factors and survival outcome. Results Sixty-two (62) patients were included in the study with a median follow-up of 20.5 months. Median age at diagnosis is 33 years and 95% of patients are from Malay ethnic group. Nonseminomatous Germ-cell tumor (NSGCT) is the most common tumor subgroup comprising 66.1%. More than 65% of patients presented with metastatic disease at presentation. Five-year OS is 68.4%, 64.2% and 33.3% for NSGCT, seminoma and non-germ cell tumor (NGCT)respectively. Five-year PFS is 51.0%, 41.0% and 26.7% for NSGCT, seminoma and NGCT respectively. Co-existing Diabetes/ hypertension (HR= 3.72, 95% CI: 1.52 – 9.11; p= 0.004), Non-germ cell histology (HR= 4.11, 95% CI: 1.52 – 11.14; p= 0.005) and presence of spermatic cord invasion (HR= 3.30, 95% CI: 1.12 – 9.77; p=0.031) are associated with poor OS. Age group 51 to 60 years is the only predictive factor for poorer OS (HR= 9.65, 95% CI: 2.05 – 45.5; p= 0.004) and PFS (HR= 10.25, 95% CI: 2.29 – 45.9; p= 0.002). Conclusion Testicular cancer is a rare disease which mainly affects young Malay males. NSGCT is the commonest subtype encountered and is associated with the highest OS and PFS. Age 51 to 60 is associated with worse OS and PFS. Meanwhile, co-existing Diabetes or hypertension, non-Germ cell histology, and presence of spermatic cord invasion are predictors of poor OS.